2020
DOI: 10.1007/978-3-030-44575-1_11
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Psychological Well-being After Union Dissolution: Does Involved Fatherhood Have a Protective Effect?

Abstract: Although the attention scholars have paid to the question of how the involvement of fathers affects the well-being of their children in post-separation families has increased tremendously in recent years, the question of how fathers’ involvement affects their own well-being has been hardly examined. Using data from the cross-sectional survey “Fathering after Union Dissolution,” which was conducted in Lithuania in 2016 (N = 1225), we looked at the extent to which the involvement of fathers with their non-reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Child development in Lithuania resembles that in other homogeneous European communities (Kaniušonytė and Žukauskienė, 2018), although some of the mothers in the current study were raised when the country was part of the Soviet Union, during a time when obedience was a priority (Gorlizki and Khlevniuk 2020). Most Eastern European countries still report higher levels of "traditional" parenting, compared to their Western European counterparts (Maslauskaitė and Steinbach, 2020). The extent to which traditional parenting encompasses friendship disapproval is not clear.…”
Section: Discussionmentioning
confidence: 96%
“…Child development in Lithuania resembles that in other homogeneous European communities (Kaniušonytė and Žukauskienė, 2018), although some of the mothers in the current study were raised when the country was part of the Soviet Union, during a time when obedience was a priority (Gorlizki and Khlevniuk 2020). Most Eastern European countries still report higher levels of "traditional" parenting, compared to their Western European counterparts (Maslauskaitė and Steinbach, 2020). The extent to which traditional parenting encompasses friendship disapproval is not clear.…”
Section: Discussionmentioning
confidence: 96%
“…In accordance with these assumptions, previous research has found significant differences in the overall adjustment of custodial and noncustodial fathers, as "[t]he presence of children appears to be a stabilizing force in the adjustment of custodial fathers, lessening detrimental effects and making them remarkably similar to their married counterparts" (Stewart & Schwebel 1986: 61-62). Moreover, noncustodial fathers have been found to fare, on average, worse than custodial parents on several health outcomes, including depression, anxiety, emotional health, and life satisfaction (Evenson & Simon 2005;Maslauskaite & Steinbach 2020;Stewart & Schwebel 1986). Similarly, in a sample of recently divorced fathers, fathers with either full physical custody or joint physical custody were found to have significantly higher levels of emotional well-being than, for example, noncustodial fathers (Bokker 2006).…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…For fathers, having either no contact or only limited contact with their children, a poor fatherchild relationship, and the perceived inability to fulfil normative expectations regarding their parental role may lead to a substantial decline in well-being (Evenson & Simon, 2005;Leopold, 2018;Leopold & Kalmijn, 2016). Consistent with these considerations, research has found that non-custodial fathers fare, on average, worse than custodial fathers on measures of depression, anxiety, emotional health and life satisfaction (Evenson & Simon, 2005;Maslauskaite & Steinbach, 2020;Stewart & Schwebel, 1986). In contrast, fathers with full physical custody or joint physical custody appear to have significantly higher levels of emotional well-being than, for example, non-custodial fathers (Bokker, 2006).…”
Section: Joint Physical Custody and Child Well-beingmentioning
confidence: 99%